ANALISIS APLIKASI E-REKON-LK TERHADAP REKONSILIASI LAPORAN KEUANGAN PADA KANTOR WILAYAH DIREKTORAT JENDERAL PERBENDAHARAAN NEGARA PROVINSI UTARA - Oflagi, Jean Gabril; Manossoh, Hendrik; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
In order to realize an effective, efficient, accurate, accountable, and transparent Central Government Financial Report, Online Reconciliation System is required to ease the Local Government, The State Ministry/Institute and Regional Office of General Directorate of Budget Financing. This study aims to investigate the process of reconciliation using the electronic reconciliation aplications (e-Rekon-LK). Research method used in this study is descriptive analysis method. This research stated that electronic reconciliation based on website application makes the reconciliation process easier where the financial statement only exist at the lowest level between Local Government and Treasury Office that conducts to all the financial data transactions to fulfill the effectiveness and efficiency, also the accountability and transparency in financial statement. However, it has some obstacles where people doesn’t really understand and being precise in doing it and also because of the internet in some places is not working properly.Keywords : Reconciliation, e-Rekon-LK